2012
DOI: 10.1080/01292986.2012.701317
|View full text |Cite
|
Sign up to set email alerts
|

Picturing terrorism through Arabic lenses: a comparative analysis of Al Jazeera and Al Arabiya

Abstract: This study examines the coverage of terrorism in two leading Arab news websites, Al Jazeera and Al Arabiya . It finds that the stereotype that 'the terrorist is a Muslim' continues in terrorism coverage, despite the fact that some terrorists are non-Muslims. However, the two sites manage to send out the message that 'the majority of terrorism victims are Muslims.' In addition, the findings reveal that too much media focus is placed on disseminating and supporting official positions and decisions, and humanitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Also, AJE in its Vision, Mission and Values icon on its website identifies its main purpose to "maintain credibility through impartial, accurate and comprehensive representation of the story" (Al Jazeera English website, 2014). Thus, the main goal of AJ is to be an objective network and produce more professional content to its audience and this main goal matches with the findings of other scholars (e.g., Boyd-Barrett & Xie, 2008;El-Nawawy & Iskandar, 2003;Quinn & Walters, 2004;Zeng & Tahat, 2012) who found that AJ is free, independent, objective and adopting Western professional values in news production. The top editorial leaders in both AJE and AJA have insisted that Al Jazeera has a completely independent editorial policy from the Qatari government, which has nothing to do with the content (Attard, 2012).…”
Section: Al Jazeera's Mission Vision and Valuessupporting
confidence: 84%
See 1 more Smart Citation
“…Also, AJE in its Vision, Mission and Values icon on its website identifies its main purpose to "maintain credibility through impartial, accurate and comprehensive representation of the story" (Al Jazeera English website, 2014). Thus, the main goal of AJ is to be an objective network and produce more professional content to its audience and this main goal matches with the findings of other scholars (e.g., Boyd-Barrett & Xie, 2008;El-Nawawy & Iskandar, 2003;Quinn & Walters, 2004;Zeng & Tahat, 2012) who found that AJ is free, independent, objective and adopting Western professional values in news production. The top editorial leaders in both AJE and AJA have insisted that Al Jazeera has a completely independent editorial policy from the Qatari government, which has nothing to do with the content (Attard, 2012).…”
Section: Al Jazeera's Mission Vision and Valuessupporting
confidence: 84%
“…Besides, this study addresses the question that has arisen about whether or not AJ has an ideological balance in its news websites (Abudl-Mageed & Herring, 2008). It also addresses the suggestion by Zeng and Tahat (2012) that future research "compare the trends of coverage between the Arabic version and English version of the same news organization" (p. 445).…”
Section: Statement Of the Problem And The Purposementioning
confidence: 93%
“…Abdullah and Elareshi (2015) indicated that both Al Jazeera Arabic and Al Arabiya news channels did not stress on the humanitarian side while reporting terrorism. Similarly, Zeng and Tahat (2012) argued that the humanitarian sufferings from terrorism were seldom brought to the attention of the public in Al Jazeera and Al Arabiya news. …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Zeng, and Tahat (2012) argued that too much media focus was placed on disseminating and supporting official positions and decisions in Al Jazeera Arabic and Al Arabiya news channels, as well as the Greek media (Protopapas, 2012).…”
mentioning
confidence: 99%
“…Finally, we chose two sources -Al Jazeera and Al Arabiya -for our Arab news sources for several reasons. 3 They are the two most popular pan-Arab news websites and are considered agenda-setters in the region (Zeng and Tahat, 2012). But Al Jazeera attempts to present information in an explicitly non-Western way and it is considered more sensational and less pro-Western than its main competitor, Al Arabiya (Nisbet and Myers, 2011;Zeng and Tahat, 2012).…”
Section: Methodsmentioning
confidence: 99%